First Record of Oceanic Anoxic Event 1d at Southern High Latitudes: Sedimentary and Geochemical Evidence From International Ocean Discovery Program Expedition 369. Issue 10 (11th May 2022) - Fan, Qingchao; Xu, Zhaokai; MacLeod, Kenneth G.; Brumsack, Hans‐Jürgen; Li, Tiegang; Chang, Fengming; Wan, Shiming; Riquier, Laurent; Fu, Delong; Luan, Zhendong; Duan, Baichuan; Chen, Hongjin; et al.
Abstract: Oceanic anoxic event 1d (OAE 1d) has been well studied at northern low latitudes (i.e., in Tethys and the North Atlantic); however, the paleoenvironmental response to this event at high latitudes has not been documented and the triggering mechanism remains unknown. Here, we address both of these shortcomings by presenting the first detailed sedimentary and multi‐proxy geochemical record of the OAE 1d at southern high latitudes (60–62°S), obtained from sediments using Site U1513, IODP Expedition 369. Biostratigraphic and chemostratigraphic data support correlation of the interval studied with OAE 1d, and the sedimentary mercury proxy reveals that at least at Site U1513, OAE 1d is associated with the Central Kerguelen large igneous province volcanism. Furthermore, the significant increase in continental runoff and consequent terrigenous input from southwestern Australia in the southeastern proto‐India Ocean might have resulted in regionally weakened bottom‐water oxygenation and strengthened organic matter burial during OAE 1d. Plain Language Summary: Geological marine records hold valuable information that could inform predictions for the future of our warming world. Marine sediments are an important reservoir of the global organic carbon and changes at the seafloor can modulate release of CO2 into the atmosphere. Cretaceous oceanic anoxic event 1d (∼latest Albian) was a significant disturbance to the global carbon cycle in the mid‐Cretaceous although it is poorly documented in the southern hemisphere especially at high latitudes. Our integrative sedimentary‐geochemical study demonstrates that oceanic anoxic event 1d at southern high latitudes might have been directly triggered by Central Kerguelen large igneous province volcanism. Volcanic emissions are proposed to have shifted the climate such that runoff and input of terrigenous sediment from southwestern Australia increased. These changes would have weakened bottom‐water oxygenation and increased organic matter burial in the southeastern proto‐Indian Ocean. Key Points: We present the first sedimentary and geochemical records for oceanic anoxic event 1d at southern high latitudes (60–62°S) Environmental changes during oceanic anoxic event 1d might be directly triggered by Central Kerguelen large igneous province volcanism Multiple paleoenvironmental changes occurred in the study area during oceanic anoxic event 1d